2020
DOI: 10.1080/17453674.2020.1745423
|View full text |Cite
|
Sign up to set email alerts
|

Single-stage debridement with implantation of antibiotic-loaded calcium sulphate in 34 cases of localized calcaneal osteomyelitis

Abstract: Background and purpose — The successful eradication of calcaneus infection with limb salvage remains a challenge. We describe the outcomes of cortical bone windowing followed by eggshell-like debridement and implantation of antibiotic-loaded calcium sulphate (CS) for localized (Cierny–Mader type III) calcaneal osteomyelitis (CO). Patients and methods — We report a retrospective study of 34 patients. Infection followed trauma or orthopedic surgery in 30 patients and hematogenous spread in 4 patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 25 publications
1
18
3
Order By: Relevance
“…21 More recently, the management of osteomyelitis in dedicated multidisciplinary bone infection units have been shown to produce better results illustrating the highly specialised nature of this work. [22][23][24] Similar results were seen in our series with successful eradication of infection in all Cierny and Mader anatomical types in 94% of cases using a single-stage approach and a tailored dead space management strategy. Apart from obviating the need for second surgery, single-stage management of chronic osteomyelitis is also more cost-effective and has been shown to offer similar if not better clinical outcomes in resolution rates of infection.…”
Section: Discussionsupporting
confidence: 81%
“…21 More recently, the management of osteomyelitis in dedicated multidisciplinary bone infection units have been shown to produce better results illustrating the highly specialised nature of this work. [22][23][24] Similar results were seen in our series with successful eradication of infection in all Cierny and Mader anatomical types in 94% of cases using a single-stage approach and a tailored dead space management strategy. Apart from obviating the need for second surgery, single-stage management of chronic osteomyelitis is also more cost-effective and has been shown to offer similar if not better clinical outcomes in resolution rates of infection.…”
Section: Discussionsupporting
confidence: 81%
“…In our study, the infection eradication rate was 94.29%, while the recurrence rate was low. Jiang et al reported that the incidence of aseptic wound exudation in the treatment of localized calcaneal osteomyelitis with calcium sulfate alone was 32.35% (11/34 patients) [17]. In comparison, our incidence of aseptic wound exudation was 2.86% (1/35 patients), which was lower compared to previous that ranged from 6.00% (6/100) [18] to 33.33% (7/21) [19].…”
Section: Discussioncontrasting
confidence: 70%
“…All the included 16 studies were published between 2002 and 2021 [ 15 , 23 , 25 , 29 41 ]. Of the included studies, three consecutive case–control studies were retrospective in nature; the remaining were case series, including 2 prospective studies and 11 retrospective studies.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the inconsistency on the properties of CS materials and surgical procedures, aseptic wound leakage and re-fracture have gradually got increasing attention, which may become the causes of reoperation or infection recurrence [ 22 ]. Jiang et al [ 23 ] found that the incidence of aseptic wound leakage after antibiotic-loaded CS implantation treated COM was very high. Therefore, in this review, we comprehensively evaluate the efficacy and complications of CS loaded with multiple antibiotics in the treatment of COM (including delayed healing, reoperation, refracture and aseptic wound leakage).…”
Section: Introductionmentioning
confidence: 99%